Genetic epidemiology of muscular dystrophies resulting from sarcoglycan gene mutations. Issue 12 (December 1997) - Fanin, M; Duggan, D J; Mostacciuolo, M L; Martinello, F; Freda, M P; Sorarù, G; Trevisan, C P; Hoffman, E P; Angelini, C
Abstract : BACKGROUND: The autosomal recessive limb-girdle muscular dystrophies (LGMDs) are a group of genetically heterogeneous muscle diseases characterised by progressive proximal limb muscle weakness. Six different loci have been mapped and pathogenetic mutations in the genes encoding the sarcoglycan complex components (alpha-, beta-, gamma-, and delta-sarcoglycan) have been documented. LGMD patients affected with primary "sarcoglycanopathies" are classified as LGMD2D, 2E, 2C, and 2F, respectively. METHODS: A geographical area in north east Italy (2, 319, 147 inhabitants) was selected for a genetic epidemiological study on primary sarcoglycanopathies. Within the period 1982 to 1996, all patients living in this region and diagnosed with muscular dystrophy were seen at our centre. Immunohistochemical and immunoblot screening for alpha-sarcoglycan protein deficiency was performed on all muscle biopsies from patients with a progressive muscular dystrophy of unknown aetiology and normal dystrophin. Sarcoglycan mutation analyses were conducted on all patient muscle biopsies shown to have complete or partial absence of alpha-sarcoglycan immunostaining or a decreased quantity of alpha-sarcoglycan protein on immunoblotting. RESULTS: Two hundred and four patient muscle biopsies were screened for alpha-sarcoglycan protein deficiency and 18 biopsies showed a deficiency. Pathogenetic mutations involving one gene for sarcoglycan complex components were identified in 13 patients: alpha-sarcoglycan in seven, beta-sarcoglycan in two, gamma-sarcoglycan in four, and none in the delta-sarcoglycan gene. The overall prevalence of primary sarcoglycanopathies, as of 31 December 1996, was estimated to be 5.6 x 10(-6) inhabitants. CONCLUSION: The prevalence rate estimated in this study is the first to be obtained after biochemical and molecular genetic screening for sarcoglycan defects.